Insights on copper, manganese, and Nickel/ZSM-5 catalytic mechanisms for nitric oxides selective reduction with ammonia - Cheng Liu (KeAi Communications Co., Ltd., 2022)
The elucidation of the selective catalytic reduction mechanisms over state-of-the-art metal-promoted zeolites is essential for nitric oxides removal in automobile and stationary source applications. In this work, H/ZSM-5 catalysts modified with transition metals, including copper, manganese, and nickel, were prepared by using an incipient wetness impregnation method and were evaluated for the selective reduction of nitric oxides with ammonia. Results indicate that copper/ZSM-5 exhibits the highest catalytic activity, with > 90% nitric oxide conversion at a broad operation temperature window (221–445 °C). The nitric oxide conversion profiles of nickel/ZSM-5 shows two peaks that correspond to weak activity among the catalysts; the low-temperature peak (290 °C) was induced by nickel clusters dispersed on the ZSM-5 surface, while the high-temperature peak (460 °C) was assigned to the bulk nickel oxides. The size of granular nickel monoxide crystallites with an exposed (2 0 2) plane is 2–30 nm, as confirmed by Scanning electron microscopy, X-ray diffraction, and Transmission electron microscope measurements. Temperature-programmed reductions with hydrogen results testified that the copper and nickel cations, as the main species contributing to selective catalytic reduction, were reduced via Cu2+/Cu+→Cu0 and Ni2+→Ni0 for copper/ZSM-5 and nickel/ZSM-5, respectively, while for the manganese/ZSM-5, the Mn3+ species in manganese clusters were reduced to Mn2+ by hydrogen. Particularly, temperature-programmed desorption coupled with mass spectrometer (TPD-MS) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were comprehensively used to reveal the relationship between zeolite structure and catalysts’ properties for improving selective catalytic reduction. These results confirm that the ammonia is adsorbed and activated on both Brønsted and Lewis acid sites. The nitrous oxide desorbs in two stages during nitric oxide-TPD-MS measurements, corresponding to the desorption of nitric oxide bounded to amorphous clusters and the nitric oxide strongly bounded to bulk metal oxides, respectively. The selective catalytic reduction process follows the L-H mechanism at low temperatures, in which nitric oxide and ammonia molecules were adsorbed and activated on the catalyst surface. The selective catalytic reduction rates reached the maximum value of 1.8 × 108 (218 °C), 6.4 × 107 (227 °C), and 3.9 × 107 s−1 (235 °C) for copper, manganese, and nickel /ZSM-5, respectively.